Role of stem-like cells in chemotherapy resistance and relapse in pediatric T-cell acute lymphoblastic leukemia - Julia Costea; Kerstin K. Rauwolf; Pietro Zafferani; Tobias Rausch; Anna Mathioudaki; Judith Zaugg; Martin Schrappe; Cornelia Eckert; Gabriele Escherich; Jean P. Bourquin; Beat Bornhauser; Andreas E. Kulozik; et al. (Nature Communications)
Abstract T-ALL relapses are characterized by chemotherapy resistance, cellular diversity and dismal outcome. To gain a deeper understanding of the mechanisms underlying relapses, we conduct single-cell RNA sequencing on 13 matched pediatric T-ALL patient-derived samples at diagnosis and relapse, along with samples derived from 5 non-relapsing patients collected at diagnosis. This comprehensive longitudinal single-cell study in T-ALL reveals significant transcriptomic diversity. Notably, 11 out of 18 samples exhibit a subpopulation of T-ALL cells with stem-like features characterized by a common set of active regulons, expression patterns and splice isoforms. This subpopulation, accounting for a small proportion of leukemia cells at diagnosis, expands substantially at relapse, indicating resistance to therapy. Strikingly, increased stemness at diagnosis is associated with higher risk of treatment induction failure. Chemotherapy resistance is validated through in-vitro and in-vivo drug testing. Thus, we report the discovery of treatment-resistant stem-like cells in T-ALL, underscoring the potential for devising future therapeutic strategies targeting stemness-related pathways.